Determination of the Radius of Cracking Zones in a Rock Mass by Explosions of Charges - Abdullayevich, Khasanov Obid; ugli, Normamatov Humoyiddin Kholmomin (European Journal of Life Safety and Stability (2660-9630), 2022)
The paper presents graphs of the maximum radius of crack formation within a rock mass relative to the explosive charge radius, explosion conditions, mass acoustic stiffness, Poisson’s ratio, and radial directional stresses occurring during compression.